OPEN WATER AND THE CIRCUMPOLAR TROUGH IN THE ANTARCTIC - エノモト, ヒロユキ; オオムラ, アツム; ENOMOTO, Hiroyuki; OHMURA, Atsumu (National Institute of Polar Research, 1992)
P(論文) The extent of open water area in spring and time of rapid retreat of the sea ice area in late spring are important characteristics of the sea ice area in the Antarctic. The present study investigates relationships between atmospheric conditions and open water extent. In the present study, the position and intensity of the circumpolar trough are used as a measure of atmospheric conditions over the sea ice area. When the circumpolar trough is intense, it tends to be located at higher latitudes along the Antarctic coast. In such cases, the open water in spring increases and the time of significant retreat of the sea ice edge in late spring tends to be delayed. departmental bulletin paper